A multi-motivational general model of entrepreneurial intention - Douglas, Evan J.; Shepherd, Dean A.; Venugopal, Vidhula (Journal of Business Venturing, 2021)
We develop and test an overarching model of entrepreneurial intention that includes profit, social impact, and innovation as the three main drivers of entrepreneurial behavior. A holistic model is developed to identify separately the generic intention to be a self-employed entrepreneur from the associated intention to be a specific type of entrepreneur. The latter is revealed by using a conjoint experiment to reveal the individual's relative preferences for profit, social impact, and innovation outcomes. Using fuzzy-set qualitative comparative analysis we provide insights into individuals' motivations for different types of entrepreneurial careers and for their multiple pathways to the same entrepreneurial type.